Electrochemical Study of Inhibition for Low Carbon Steel Corrosion in the Saline Medium through a Novel Polymer-metal oxides Nanocomposite - Hussain, Zainab; Saleh, Khulood A. (Iraqi Journal of Science, 2025)
In this work, new conductive polymer (4900 µs.cm-1) poly 6-((4-sulfamoylphenyl)carbamoyl)cyclohex-3-ene-1-carboxylic acid (PSCC) was prepared on a Low Carbon Steel (L.C.S) surface by an electrochemical polymerization process for its monomer 6-((4-sulfamoylphenyl)carbamoyl)cyclohex-3-ene-1-carboxylic acid (SCC) to study the effect of this polymer against corrosion of the L.C.S in salt environment (3.5% wt NaCl) at four temperatures; 25, 35, 45, and 55 oC. Two types of nanometal oxides, ZrO2 and ZnO, were applied as additives to the polymer (PSCC) to enhance the ability of this polymer on corrosion protection L.C.S alloy. Potentiostatic polarization tests evaluated the corrosion performance of the coatings. Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) study the coatings’ topography and morphology of the surfaces. The study determined and analyzed the kinetic and thermodynamic parameters associated with the activation energy required for the corrosion reaction to occur. The results indicate that the prepared polymer effectively reduced the corrosion of L.C.S, and the addition of nanometal oxides further enhanced the polymer’s performance in protecting the alloy from corrosion.